Diagnosis of major heart defects by routine first‐trimester ultrasound examination: association with increased nuchal translucency, tricuspid regurgitation and abnormal flow in ductus venosus. (1st May 2020) - Minnella, G. P.; Crupano, F. M.; Syngelaki, A.; Zidere, V.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the association between fetal major heart defects and increased nuchal translucency thickness (NT), tricuspid regurgitation and abnormal flow in the ductus venosus in a large population of singleton pregnancies undergoing routine ultrasound examination at 11–13 weeks' gestation. Methods: This was a retrospective study of prospectively collected data from singleton pregnancies attending for a routine ultrasound scan at 11–13 weeks' gestation, which included examination of fetal anatomy, measurement of NT and assessment of blood flow across the tricuspid valve and in the ductus venosus, according to a standardized protocol. The incidence of fetal NT ≥ 95 th and ≥ 99 th percentiles, tricuspid regurgitation and reversed a‐wave in the ductus venosus in fetuses with and those without a major heart defect was determined and the performance of each marker and their combination in the detection of major heart defects was calculated. Results: The study population of 93 209 pregnancies with no apparent chromosomal abnormality included 211 (0.23%) with a fetal major heart defect and 92 998 morphologically normal neonates. In 113 (53.6%) cases with a major heart defect, the diagnosis was made at the 11–13‐week scan, in 82 (38.9%) at the 18–24‐week scan, in 10 (4.7%) at the third‐trimester scan and in six (2.8%) postnatally. At the 11–13‐week scan, we diagnosed all cases of tricuspid or pulmonary atresia and polyvalvular dysplasia, > 90% of cases of hypoplastic left heart syndrome or atrioventricular septal defect, about 60% of complex heart defects and cases of left atrial isomerism (interrupted inferior vena cava with normal intracardiac anatomy), 30–40% of cases of tetralogy of Fallot and arch abnormalities, 25% of tricuspid valve abnormalities and about 15% of cases of transposition of the great arteries, but none of aortic or pulmonary stenosis or common arterial trunk. Fetal NT ≥ 95 th or ≥ 99 th percentile, tricuspid regurgitation or abnormal ductus venosus flow was observed in 77 (36.5%), 45 (21.3%), 61 (28.9%) and 58 (27.5%) fetuses with a major heart defect, respectively, and in 5678 (6.1%), 857 (0.9%), 1136 (1.2%) and 1644 (1.8%) of those without a heart defect. Any one of NT ≥ 95 th percentile, tricuspid regurgitation or abnormal flow in the ductus venosus was found in 117 (55.5%; 95% CI, 48.5–62.3%) fetuses with a heart defect and in 8166 (8.8%; 95% CI, 8.6–9.0%) of those without a heart defect. Any one of NT ≥ 99 th percentile or the other two markers was found in 99 (46.9%; 95% CI, 40.0–53.9%) fetuses with a heart defect and in 3517 (3.8%; 95% CI, 3.7–3.9%) of those without a heart defect. Conclusion: At 11–13 weeks' gestation, measurement of fetal NT and assessment of flow across the tricuspid valve and in the ductus venosus can lead to early diagnosis of major heart defect. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.